Effect of Mixed Isocyanate Curing Agents on the Performance of In Situ‐Prepared HTPE Binder Applied in Propellant. Issue 3 (27th January 2021) - Chen, Keke; Yuan, Shen; Wen, XiaoMu; Sang, Chao; Luo, Yunjun
Abstract: A novel hydroxyl‐terminated block copolymer (HTPE) binder was prepared through an in situ preparation method to replace the traditional HTPE binder. The preparation method is less costly and bypasses the preparation of the HTPE prepolymer intermediate, thus avoiding the complicated prepolymer synthesis process. Uniaxial tensile testing, low‐field nuclear magnetic resonance, and infrared spectroscopy were used to investigate the mechanical properties, curing networks, and hydrogen bonding (H‐bonds) of the binder. The crosslink density ( Ve ) decreased with an increase in the ratio of −NCO in the IPDI to the total −NCO in the IPDI and N100 (χ). The proportion of H‐bonds formed by the imino groups increased with the IPDI content and reached 86.53 % at a χ value of 90 %, indicating a positive correlation between the H‐bonds and σm . Additionally, to study the pot life of the in situ‐prepared HTPE binder, the rheological properties of the curing reactions were studied. When the χ value was in the range of 50 %–90 %, the pot life of the binder met the composite propellant requirements for military applications. The thermal decomposition behaviors of the in situ‐prepared HTPE binder and the traditional HTPE binder were investigated by the coupling analysis of thermogravimetry‐Fourier transform infrared spectroscopy (TG‐FTIR), and the novel in situ‐prepared HTPE binder exhibited good thermal stability and superior energetic performance. Compared with the traditional HTPE‐based propellant, the mechanical properties of the in situ‐prepared‐HTPE‐based propellants were greatly improved. With these data, the in situ‐prepared HTPE binder has great potential for application in rocket propellant formulations. Abstract :